Planar or tetrahedral? A ternary 17-electron CBe5H4+ cluster with planar pentacoordinate carbon - Guo, Jin-Chang; Feng, Lin-Yan; Barroso, Jorge; Merino, Gabriel; Zhai, Hua-Jin (Chemical communications (Cambridge, England), 2020)
A 17-electron CBe5H4+ cluster features planar pentacoordinate carbon, owing to the 2π/6σ double aromaticity. The neutral CBe5H4 cluster has a tetrahedral configuration despite its 18-electron counting. The latter species is governed by σ conjugation.